Incidence and Impact of Land Conflict in Uganda - Deininger, Klaus; Castagnini, Raffaella (World Bank, Washington, D.C., 2013)
While there is a large, though inconclusive, literature on the impact of land titles in Africa, little attention has been devoted to the study of land conflict, despite evidence on increasing incidence of such conflicts. The authors use data from Uganda to explore who is affected by land conflicts, whether recent legal changes have helped to reduce their incidence, and to assess their impact on productivity. Results indicate that female-headed households and widows are particularly affected and that the passage of the 1998 Land Act has failed to reduce the number of pending land conflicts. The authors also find evidence of a significant and quantitatively large productivity-reducing impact of land conflicts. This suggests that, especially in Africa, attention to land-related conflicts and exploration of ways to prevent and speedily resolve them would be an important area for policy as well as research.